Peningkatan K3 dan Produktivitas Pekerja Konstruksi pada Proyek Rumah Kos - Talitha Hafira; Nur Fithriani Fatma Cholida; Iryan Dwi Handayani; Widya Ayu Prawesthi (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
This community service activity was motivated by the low awareness of construction workers towards K3 in a small-scale boarding house construction project in Wanamukti, Tembalang, Semarang, where the construction sector contributes >30% of national work accidents due to minimal use of PPE and supervision. The problem formulation includes low knowledge ofK3, non-compliance with PPE, and the absence of simple SOPs that lead to high risks and low productivity. The program's objective is to improve understanding, skills, and a safe work culture through training and mentoring. The research method consisted of an initial survey, a pretest with 15 workers, applied K3 training with PPE demonstrations and safety talks, field mentoring, and a posttest using the N Gain formula. The results showed an increase in posttest scores from the range of 30–60 to 70–95 (100% of participants increased), with an average N Gain of 56.78% (moderate category); workers began to get used to wearing helmets, safety shoes, and gloves, and a decrease in unsafe acts. The conclusion is that the training is effective in improving safety and productivity. Suggestions for future service include continuing regular training, developing K3 SOPs, and expanding to similar projects in several other cities.